If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 7 = 4t + -9 Reorder the terms: 7 + 5t = 4t + -9 Reorder the terms: 7 + 5t = -9 + 4t Solving 7 + 5t = -9 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 7 + 5t + -4t = -9 + 4t + -4t Combine like terms: 5t + -4t = 1t 7 + 1t = -9 + 4t + -4t Combine like terms: 4t + -4t = 0 7 + 1t = -9 + 0 7 + 1t = -9 Add '-7' to each side of the equation. 7 + -7 + 1t = -9 + -7 Combine like terms: 7 + -7 = 0 0 + 1t = -9 + -7 1t = -9 + -7 Combine like terms: -9 + -7 = -16 1t = -16 Divide each side by '1'. t = -16 Simplifying t = -16
| -1=3r+2r | | 0.5(6x+18)=3(x+3) | | (6x+18)=3(x+3) | | 5+4p=5(p+2) | | .25(20-4a)=6-a | | 3x-3=-3x+-3 | | -5c+6=9-4c | | -10x+6=-7x+-9 | | .5x+1.2=4x-3.05 | | 17-8b=3b-5 | | 5r+9=2r-12 | | -8c+21=2c+1 | | (x+6)-(x-4)(x-4)=0 | | 2x+14=5-x | | 3(7-2x)=14-8(x-1) | | 5(3x-2)=3(5x-1) | | (x-9)(x+9)=(x-1)(x-1) | | 48-4x=5x+20 | | 6-10x=21-17x | | -108-8x=8x+20 | | 6x+9=89-8x | | W-4w=2w+1-5w | | 120-4x=3x+15 | | 11-2x=5-5x | | -34-2x=6-10x | | 14-(2x+5)=-2x+9 | | 76-3x=7x+16 | | 5x+10=80-2x | | 8+12x=140+x | | 4(a-3)+2=3a-19 | | 2x-3=11x-93 | | 3x+24=10x-39 |